Impacts of supply chain collaboration on supply chain risk management capabilities for operational performance: a buyer-supplier perspective - Luo, PW (2022)
Against the backdrop of increasingly complex global supply chains and an uncertain external environment, effective risk management is a high priority in almost every dynamic business. Due to the ripple effect of modern supply chains, no business in the supply chain is immune to SC disruption. As a result, key players need to build partnerships with their suppliers to stop and respond to the propagation of breakdowns in the SC, thereby maintaining their own operational performance. This study aims to empirically investigate how collaboration between buyers and suppliers can improve operational performance by enhancing SCRM capabilities, exploring the underlying mechanisms and interdependencies of these three factors in supply chain practices. Survey data from 279 Chinese manufacturer companies were collected and analysed using the SmartPLS v.3.2.3 package. The results not only confirm that the fundamental principles of resource-based perspectives, dynamic capabilities and information processing theory are helpful in dealing with uncertain events, but also illustrate the positive role of SCC in enhancing SCRM capabilities and improving the operational performance of companies. It also reveals the mediating effects of SCRM capabilities. Overall, this research will contribute to the literature in the field of SCC and SCRM, and help companies understand integrated and collaborative approaches to improving operational performance.